Association between willingness to deprescribe and health outcome priorities among U.S. older adults: Results of a national survey. Issue 10 (6th June 2022) - Green, Ariel R.; Aschmann, Hélène; Boyd, Cynthia M.; Schoenborn, Nancy
Abstract: Background: It is not known whether older adults' willingness to deprescribe is associated with their health outcome priorities related to medications. Methods: A cross‐sectional survey was conducted from March–April 2020 using a nationally representative online panel. The survey presented two vignettes: (1) a preventive medicine; and (2) a symptom‐relief medicine. Participants were asked whether they would be willing to stop each medicine if their doctor recommended it, and to rate their level of agreement with two health outcome priorities statements: "I am willing to accept the risk of future side effects … to feel better now, " and "I would prefer to take fewer medicines, even if … I may not live as long or may have bothersome symptoms sometimes." Ordinal logistic regression was used to examine associations between willingness to stop each medicine, baseline characteristics and health outcome priorities. Results: Of 1193 panel members ≥65 years invited to participate, 835 (70%) completed the survey. Mean (SD) age was 73 years; 496 (59%) had taken a statin and 124 (15%) a prescription sedative‐hypnotic. 507 (61%) were willing to stop preventive medicines; 276 (33%) were maybe willing. 419 (50%) were willing to stop symptom‐relief medicines; 380 (46%) were maybe willing. Prioritizing fewer medicines was associated with higher odds of being willing to stop symptom‐relief medicines (aOR 1.43 [95% CI 1.02–2.00]) and preventive medicines (aOR 1.52 [95% CI 1.05–2.18]). Prioritizing now over future was associated with lower odds of being willing to stop symptom‐relief medicines (aOR 0.62 [95% CI 0.39–1.00]). Current/prior use of statins was associated with lower willingness to stop preventive medicines (aOR 0.66 [95% CI 0.48–0.91]). Conclusions: Older adults' health outcome priorities related to medication use are associated with their willingness to consider deprescribing. Future research should determine how best to elicit patients' health outcome priorities to facilitate goal‐concordant decisions about medication use.